Uso de metacaulim como fonte de alumina em escórias visando à produção de cimento supersulfatado - Pimenta, Samuel Fernandes (2020)
The production of Portland cement (PC) is responsible for about 5 to 8% of CO2emitted on the planet, a considerable percentage when thought that cement is one of the most used materials in the world. In addition to this unfavorable outlook, it should be noted that in order to obtain the PC, it requires a large amount of non-renewable raw material and high energy expenditure. Given this view of science for practices that are less aggressive to the environment, the use of other cements is highlighted, among them, supersulfated cement (SSC). Consisting of 70-90% of blast furnace slag (by-product of the steel industry), 10-20% of calcium sulfate and up to 5% of an alkaline activator (usually PC), SSChas the advantage of using by-products other industrial segments, its low energy expenditure and great resistance to chemically aggressive environments. Previous studies have shown that blast furnace slag with a high content of Al2O3(>13%) may show better reactivity and greater formation of etringite, providing better mechanical performance at early ages, however, Brazilian slags have an average content of Al2O3(7 to11%), which may compromise the resistance of the SSC. In this sense, the objective of this work was to use metakaolin (MK) as an alternative source of Al2O3 in SSC. For this purpose, SSCpastes were prepared with partial blast furnace slag replacements by MK (0, 5, 10, 15 and 20%) and tests were performed for mechanical strength, calorimetry, water absorption, X-ray diffractometry (XRD) and thermogravimetric (TG-DTG). The best results of mechanical resistance were presented by the sample with 5% of MK at all ages, however the samples with 10% were compared to the reference sample (0% of MK). Samples with 15 and 20% had results lower than the reference sample. Through microstructure analysis (XRDand TG-DTG) it was possible to evaluate the characterization of the pastes and to identify the presence of etringite (object of study) in all samples and at all ages. However, it was possible to observe a higher intensity of hydrate in pastes with 5 and 10% MK. Thus, it is possible to verify that MK is a viable alternative for improving the mechanical resistance of SSC, when used by up to 10%, but it is possible to consider that MK is restricted to an optimum content.